NIR‐Actuated Remote Activation of Ferroptosis in Target Tumor Cells through a Photothermally Responsive Iron‐Chelated Biopolymer Nanoplatform. (8th March 2021) - Xue, Chencheng; Li, Menghuan; Liu, Changhuang; Li, Yanan; Fei, Yang; Hu, Yan; Cai, Kaiyong; Zhao, Yanli; Luo, Zhong
Abstract: Ferroptosis is a new form of regulated cell death that shows promise for tumor treatment. Most current ferroptosis tumor therapies are based on the intrinsic pathological features of the malignancies, and it would be of clinical significance to develop ferroptosis‐inducing strategies with improved tumor specificity and modulability. Here we report a polydopamine‐based nanoplatform (Fe II PDA@LAP‐PEG‐cRGD) for the efficient loading of Fe 2+ and β‐lapachone (LAP), which could readily initiate ferroptosis in tumor cells upon treatment with near‐infrared light. PDA nanostructures could generate mild hyperthermia under NIR irritation and trigger the release of the ferroptosis‐inducing Fe 2+ ions. The NIR‐actuated photothermal effect would also activate cellular heat shock response and upregulate the downstream NQO1 via HSP70/NQO1 axis to facilitate bioreduction of the concurrently released β‐lapachone and enhance intracellular H2 O2 formation to promote the Fe 2+ ‐mediated lipid peroxidation. Abstract : Ferroptosis is a new form of regulated cell death and holds promise for tumor inhibition. However, it is difficult to remotely control the initiation and execution of ferroptosis in specific sites. This study reports a biocompatible and biodegradable biopolymeric nanoplatform for tumor‐targeted ferroptosis therapy, of which the pro‐ferroptotic activities could be activated in an on‐demand manner using near‐infrared light as the triggering signal.